Path Analysis of Physical Symptoms, Emotional Support, Self-Esteem, and Depressive Symptoms in HIV-Positive Perinatal Women in Thailand - Ratchneewan Ross; Carolyn Kleman; Pimpanitta Saenyakul; Andrea Warner Stidham (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
Evidence shows that depressive symptoms are associated with faster progression to AIDS in HIV-infected populations. Physical symptoms, self-esteem, and emotional support have been reported to play a major role in contributing to depressive symptoms. However, comparisons of different sources of support—specifically family vs. friends— have only been made in a few previous HIV studies. Therefore, the objectives of this study among HIV-positive perinatal Thai women were to examine: 1) both the direct and indirect effects of physical symptoms and emotional support on depressive symptoms; 2) which source of support is more significant, family or friends; and 3) the direct effect of self-esteem on depressive symptoms. Results revealed that half of the participants experienced major depressive symptoms. Physical symptoms and self-esteem both had direct effects on depressive symptoms. Emotional support, from friends and family, had an indirect effect on depressive symptoms. Treating physical symptoms and increasing self-esteem through emotional support, could help decrease depressive symptoms in the target population. Finally, it is crucial that routine screening for depressive symptoms is established at all HIV clinics for perinatal women in Thailand.
Keywords: HIV